MANAJEMEN NYERI PASIEN RAWAT JALAN PADA KASUSHERNIA NUKLEUS PULPOSUS MELALUI CORE STABILITY - Roselina, Elsa; Arifin, Safrin; Gidion, Hermito (UI Scholars Hub, 2014)
Herniated nucleus pulposus (HNP) is a situation where the annulus fibrosus along nucleus pulposus protruding into the spinal canal. HNP patients often complain of back pain radiating to the lower limbs, especially when bending activity. Rehabilitation programs do to help reduce the pain. The aim of this research knew which treatment was more effective among William's Flexion compared to Core Stability in reducing pain for HNP patients. This study used a double-blind experimental design with an alpha value of 5%. The study was conducted at the Clinic “X”. Sample was 18 patients with medical diagnoses HNP undergoing therapy from September to December 2013, taken with randomization techniques. Pain was measured using the Visual Analoque Scale (VAS). The results of the t-test analysis showed that Core stability (mean=4.56, SD=1.130) was more effective than William's flexion [mean = 2.78, SD = 0.972; t(16) = - 3.578, p = 0.003] in reducing pain for HNP patients. The results of One-Way ANOVA showed that there was no significant difference in pain reduction produced by William's flexion frequency of treatment [F(2, 6)=1.857, p=0.236]. In contrast, there were significant differences in pain reduction produced by Core stability frequency treatment [F(1, 6)=12.333, p=0.007].